Consumption of sustainable medications and its impact on health - Szalonka, Katarzyna; Stańczyk, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Sustainable consumption of medicines is medically justified medicine consumption, indispensable in the treatment process, which contributes to the quality of life of the patient and extends the patient’s life resulting from the doctor’s recommendations and verified by the pharmacist (elimination of medicine interactions). The aim of this paper is to analyze differences in the level of medicines consumption in Poland and in the wider world, and its impact on life expectancy and health status. There is a large variation in the per capita medicine intake in certain countries. The following hypothesis was formulated in the paper: the consumption of medicines is not related to the health and longevity of the inhabitants. The article is based on secondary research and a statistical analysis of medicine consumptionin selected countries in the years 2015–2018. Also presented are the results of research regarding the consumption of medicines in terms of quantity and value in Poland against the background of selected countries and also in regional location in the context of socio-economic conditions.
Keywords: consumption; medications